Financial Management Training for Joglo Barat Jakarta Business Development - Lusia Sri Arini; Elok Kurniawati (Ridwan Institute, 2022)
Community service has been carried out by analyzing the situation of partners not getting used to doing financial books, how to market products that have not been arranged to attract consumers, how to offer products to consumers who are still not friendly. For this reason, service to partner catfish breeders is carried out by helping them keep records and develop their business. The activities carried out provide bookkeeping, financial management with theory and practice, marketing management, and entrepreneurship. The output of this service is so that catfish farmers are more skilled in managing their business, and it is hoped that having the above knowledge will develop more and become the goal of consumers to buy their products at this farm. After being given training, partners get financial knowledge; partners can do bookkeeping every day so that with this bookkeeping, they can design their business development. Knowledge of marketing and entrepreneurship can support a rice stall's current and future success. In the end, the development of this business will improve the standard of living and the economy of partners